Employee Work Discipline: The Effect of Reward and Punishment: Study on Employees of an Automotive Dealer Company in Bandung - Raka Ilham Septiana; Ujang Wawan Sam Adinata (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
This study investigates the effect of reward and punishment on employee work discipline. The employees at an auto dealer company in Bandung were asked questions as part of the research method. The number of respondents who participated in this study was 97 employees. The results of the study show that there is an effect of reward and punishment on work discipline. However, the effect of the reward variable on work discipline has a more minor effect than the punishment variable. The punishment variable is the dominant variable influencing work discipline; in other words, the effect of punishment on work discipline is greater than the effect of rewards on work discipline. Companies should be able to increase the punishment of employees based on such things as paying attention to clarity after making mistakes, demotions, and verbal reprimands. The hope is that optimal punishment will increase, impacting optimal discipline.